Natural products targeting ferroptosis in cancer: molecular mechanisms and applications - Ye, Xin; Ju, Xiaoli (Frontiers in Oncology, 2025)
Ferroptosis is a novel class of programmed cell death that is mainly dependent on intracellular iron accumulation and lipid peroxidation. Ferroptosis is closely related to a variety of human diseases, especially different kinds of cancer. Several small molecule inducers have been developed to induce ferroptosis in tumor cells, some of which have been used in clinical studies. However, these chemical small molecules have toxic effects that limit its wide application. Natural products, however, have a natural advantage in cancer therapy due to their low toxicity and side effects. Some natural products have been found to inhibit tumor growth by inducing ferroptosis in tumor cells. In this review, we reviewed the molecular mechanism of ferroptosis and how natural products targeting ferroptosis signaling pathways affect tumor growth. We also analyzed the application of various natural products such as flavonoids, terpenoids, and alkaloids in inducing ferroptosis in tumor cells. This review will assist in the future discovery and study of more natural product inducers that can induce ferroptosis in tumor cells, and ultimately provide insights into identifying natural products that can be applied to clinical applications.